High Prevalence of Rotavirus A in Raw Sewage Samples from Northeast Spain - Marcelle Silva-Sales; Sandra Martínez-Puchol; Eloy Gonzales-Gustavson; Ayalkibet Hundesa; Rosina Gironès (Viruses, 2020)
Rotavirus A (RVA) is the most common virus associated with infantile gastroenteritis worldwide, being a public health threat, as it is excreted in large amounts in stool and can persist in the environment for extended periods. In this study, we performed the detection of RVA and human adenovirus (HAdV) by TaqMan qPCR and assessed the circulation of RVA genotypes in three wastewater treatment plants (WWTPs) between 2015 and 2016 in Catalonia, Spain. RVA was detected in 90% and HAdV in 100% of the WWTP samples, with viral loads ranging between 3.96 × 104 and 3.30 × 108 RT-PCR Units/L and 9.51 × 104 and 1.16 × 106 genomic copies/L, respectively. RVA VP7 and VP4 gene analysis revealed the circulation of G2, G3, G9, G12, P[4], P[8], P[9] and P[10]. Nucleotide sequencing (VP6 fragment) showed the circulation of I1 and I2 genotypes, commonly associated with human, bovine and porcine strains. It is important to mention that the RVA strains isolated from the WWTPs were different from those recovered from piglets and calves living in the same area of single sampling in 2016. These data highlight the importance of monitoring water matrices for RVA epidemiology and may be a useful tool to evaluate and predict possible emergence/reemergence of uncommon strains in a region.